Anthropology and activism
1 online resource (xxi, 220 pages)
Keywords: "This book offers a comprehensive and current look at the complex relationship between anthropology and activism. Activism has become a vibrant research topic within anthropology and many scholars now embrace their own roles as engaged social actors, which has compelled reflexive attention to the anthropology/activism intersection and its implications. With contributions by emerging scholars as well as leading activist anthropologists, this volume illuminates the diverse ways in which the anthropology/activism relationship is being navigated. Chapters touch on key areas including environment and extraction, food sustainability and security, migration and human rights, health disparities and healthcare access, class and gender identities and empowerment, and the defense of democracy. Case studies (drawn mainly from North America) encourage readers to think through their own experiences and expectations and will serve as durable documentation of how movements develop and change. This timely survey of the activist anthropological landscape is valuable reading in an era of widely perceived ecological and political crisis, where disinterested data collection increasingly appears to be a luxury that neither the discipline nor the world can afford"--